Dexamethasone Intravitreal Implant at the Time of Cataract Surgery in Eyes with Diabetic Macular Edema. Issue 4 (26th June 2017) - Panozzo, Giacomo A.; Gusson, Elena; Panozzo, Giorgio; Dalla Mura, Giulia
Purpose: To determine the potential role of intraoperative dexamethasone intravitreal implant (DEX-I) in reducing diabetic macular edema (DME) worsening after phacoemulsification. Methods: This was a prospective study on 19 eyes of 19 patients with type 2 diabetes mellitus with DME and cataract. Mean preoperative Early Treatment Diabetic Retinopathy Study visual acuity (VA) was 16.7 letters. Mean foveal thickness (FT) was 451 μm. The DME was naive in 11 eyes and refractory in 8 eyes. All eyes underwent a standard phacoemulsification and intraocular lens implantation; DEX-I was injected at the end of surgery. Follow-up was performed at 1 week and then monthly until DME recurrence (up to 8 months). Results: At 1 week, mean VA improved by 15 letters (range 0-29 letters) and mean FT decreased by 147 μm (range 69-236 μm). Improvement consolidated at month 1, with a mean VA improvement of 18 letters (range 3-32 letters) and a mean improvement in FT of 193 μm (range 76-304 μm), remaining stable at month 2 after surgery in all eyes. The DME recurred in 1 eye at month 3, in 14 eyes (73.8%) between months 4 and 5, and after month 6 in 4 eyes (21%). Refractory DMEs demonstrated the same benefit but recurred earlier than naive ones (4 months versus 5.8 months, p<0.01). Conclusions: Intraoperative DEX-I prevents DME worsening after phacoemulsification. Its positive effects last for at least 3 months.